2014
DOI: 10.1016/j.jenvman.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impacts of the REDD+ pilot project on community forests user groups (CFUGs) and their community forests in Nepal

Abstract: REDD+ has the potential to reduce greenhouse gas emissions, meet climate stabilisation targets and protect biological diversity. Consequently, millions of dollars are being channelled into developing countries rich in forests, for pilot projects that will provide data for the design of REDD+ projects that are based on incentives and performance. This paper evaluates the impacts of REDD+ pilot projects on community forests and associated user groups (CFUGs) in Nepal. A field study targeted eight CFUGs that part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 14 publications
4
56
0
4
Order By: Relevance
“…Most non-REDD+ groups did not maintain good records. These findings, which suggest that REDD+ user groups were more actively engaged in making forest management decisions, confirm the findings in Poudel et al (2014).…”
Section: Management Effectivenesssupporting
confidence: 90%
“…Most non-REDD+ groups did not maintain good records. These findings, which suggest that REDD+ user groups were more actively engaged in making forest management decisions, confirm the findings in Poudel et al (2014).…”
Section: Management Effectivenesssupporting
confidence: 90%
“…Furthermore, a major review of the effects of certification found cases where it enhances land tenure security for local people (SCR, 2012). Improvements in land security are also noted for PES schemes (Tacconi et al, 2013) and in some REDD+ pilot projects Maraseni et al, 2014).…”
Section: Governance Beyond the State: Markets And Non-state Actorsmentioning
confidence: 85%
“…Carbon payments have not been made yet; it might well be lower than expected. A study on REDD+ in Nepal has shown that carbon payments were barely enough to cover the transaction costs of the local communities [61]. Moreover, 70% of the households in Kala Tonggu disagreed with the statement that REDD+ gave them more livelihood possibilities.…”
Section: Focal Action Situations and Outcomesmentioning
confidence: 99%